2015
DOI: 10.5888/pcd12.150251
|View full text |Cite
|
Sign up to set email alerts
|

Wellness Coaching for People With Prediabetes: A Randomized Encouragement Trial to Evaluate Outreach Methods at Kaiser Permanente, Northern California, 2013

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…However, while the number of consenters to the wellness coaching program was low, participant characteristics did not differ significantly from non-participants, and response rates reflect similar recruitment challenge seen in other studies. For example, Kaiser Permanente's encouragement trial that evaluated outreach methods (secured email, letter or phone) to recruit patients into Wellness Coaching Centers (SCC) showed a 1.9% overall uptake rate across the three intervention arms ( Xiao et al, 2015 ). Reaching out to potential subjects during clinic visits and bringing wellness coaching into the community are ways of possibly increasing participation rates among the high risk individuals who may benefit from it; further research on identifying barriers and facilitators to recruitment would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the number of consenters to the wellness coaching program was low, participant characteristics did not differ significantly from non-participants, and response rates reflect similar recruitment challenge seen in other studies. For example, Kaiser Permanente's encouragement trial that evaluated outreach methods (secured email, letter or phone) to recruit patients into Wellness Coaching Centers (SCC) showed a 1.9% overall uptake rate across the three intervention arms ( Xiao et al, 2015 ). Reaching out to potential subjects during clinic visits and bringing wellness coaching into the community are ways of possibly increasing participation rates among the high risk individuals who may benefit from it; further research on identifying barriers and facilitators to recruitment would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…While WO participation fell short of our target, the 23.6% (321 of 1358) uptake is considerable when contrasted with participation in PR by Medicare beneficiaries (4%) with COPD or among those who had a recent COPD hospital discharge (2.7%) or among patients exposed to lighter-touch no-cost behavioral programs (2%) . Nonetheless, health systems need to weigh the resources associated with broad outreach efforts and the yield in patient engagement, especially in response to the recent PA guidelines recommending that all older adults and those with chronic conditions engage in some level of PA .…”
Section: Discussionmentioning
confidence: 98%
“…While WO participation fell short of our target, the 23.6% (321 of 1358) uptake is considerable when contrasted with participation in PR by Medicare beneficiaries (4%) with COPD 13 or among those who had a recent COPD hospital discharge (2.7%) 12 or among patients exposed to lighter-touch no-cost behavioral programs (2%). 50 Nonetheless, health systems need to weigh the resources associated with broad outreach efforts and the yield in patient engagement, especially in response to the recent PA guidelines recommending that all older adults and those with chronic conditions engage in some level of PA. 16 When contacted, approximately 34.6% (471 of 1358) of patients in our study expressed no interest in the WO program. However, the rate of disinterested patients would increase to 57.7% (784 of 1358) if passive declines (patients who did not return our calls despite 3 contacts) were included.…”
Section: Discussionmentioning
confidence: 99%
“…In that trial, women were twice as likely as men to engage in the program, and the odds of a patient enrolling increased as the patient aged. 30 Another study of insurer-initiated outreach found that completion of an HRA did not significantly increase the likelihood of member participation in telephone-based health coaching. 31 A study of primary care physician-initiated referral to a smoking cessation program found that 7.8% of patients who were proactively contacted and asked to enroll in a program did so, while only a All the confounders are controlled by the matching process, therefore the final logistic regression only included group effect (indicator variable with 1 being Prescription for Wellness and 0 being control).…”
Section: Lessons Learnedmentioning
confidence: 99%